THE STRUGGLE FOR INDEPENDENT JUDICIARY IN SERBIA - Marković, Đorđe D. (Political Review, 2024)
The citizens of the Republic of Serbia confirmed the constitutional amendments concerning the judiciary in a referendum held in January 2022. This constitutional change is part of a long-term struggle for an independent and professional judiciary in Serbia. The paper focuses on the procedure and conditions for the election of judges and the termination of judicial office. This research study incorporates several aspects of the de jure judicial independence initially developed by Melton and Ginsburg, later expanded upon in the Serbian context by Simović. The article employed a qualitative content analysis methodology of a wide array of credible data sources such as various constitutional and legal acts, academic publications, opinions from the Venice Commission, input from professional associations, and a historical approach to examining the development of judicial independence in Serbia. A chronological analysis of the most significant constitutional provisions addressing these issues, covering the period from the late 19th century to the present, is provided. Since 2002 it was first introduced, the High Judicial Council, as an independent body of judicial self-government, has undergone significant changes in composition and competencies several times. Inasmuch as Serbia is a candidate for EU membership, the domestic and European public are interested in the judiciary becoming the veritable third branch of government, efficient and reliable. Hence, the expectations concerning the constitutional reform are high.